Spontaneous epidural spinal hematoma: case report - De Luca Druda, Otávio; Francisco Lara Júnior , Adauto (Seven Editora, 2023)
Spontaneous epidural spinal hematoma (HEEE) is a rare condition. Its estimated incidenceis 1 new case per 1,000,000 people per year1. HEEE has been associated withcoagulation disorders or vascular malformations. However, its exact etiology may not be discovered in 40 to 50% of cases2. HeeE is usually accompanied by acute cervical pain or high intensity scar injury. Depending on the location and size may be accompanied by neurological deficit. DOI: https://doi.org/10.56238/tfisdwv1-158